2013
DOI: 10.1017/s1041610212002359
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of verbal and non-verbal semantic knowledge and autobiographical memories starting from popular songs in Alzheimer's disease

Abstract: Our findings demonstrate that popular songs can be excellent stimuli for reminiscence, such as the ability to produce an autobiographical memory related to a song. Thus, we confirm that musical semantic knowledge associated with a song may be relatively preserved in the early stages of AD. This leads to new possibilities for cognitive stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…In AD, there are many striking accounts of how a person with severe dementia who is uncommunicative and mostly unresponsive to the environment can suddenly become animated and aroused when hearing a familiar song (Sacks, 2007). During the last decade, these observations have also received scientific support as experimental studies comparing AD patients and healthy elderly controls have shown that AD patients typically have relatively well-preserved ability to detect basic acoustic changes (e.g., pitch, timbre, rhythm) in music, although higher-level auditory functions, such as melodic contour perception, auditory apperception / scene analysis, and tonal working memory can be impaired (Basaglia-Pappas et al, 2013;Golden et al, 2017;Goll et al, 2011Goll et al, , 2012Johnson et al, 2011;Ménard & Belleville, 2009;White & Murphy, 1998). AD patients are also able to perceive and recognize emotions conveyed by music as well as recognize the melodies and titles of familiar songs (Drapeau, Gosselin, Gagnon, Peretz, & Lorrain, 2009;Hsieh, Hornberger, Piguet, & Hodges, 2011Johnson et al, 2011).…”
Section: Preservation Of Music-evoked Emotions and Memories In Alzheimentioning
confidence: 98%
See 1 more Smart Citation
“…In AD, there are many striking accounts of how a person with severe dementia who is uncommunicative and mostly unresponsive to the environment can suddenly become animated and aroused when hearing a familiar song (Sacks, 2007). During the last decade, these observations have also received scientific support as experimental studies comparing AD patients and healthy elderly controls have shown that AD patients typically have relatively well-preserved ability to detect basic acoustic changes (e.g., pitch, timbre, rhythm) in music, although higher-level auditory functions, such as melodic contour perception, auditory apperception / scene analysis, and tonal working memory can be impaired (Basaglia-Pappas et al, 2013;Golden et al, 2017;Goll et al, 2011Goll et al, , 2012Johnson et al, 2011;Ménard & Belleville, 2009;White & Murphy, 1998). AD patients are also able to perceive and recognize emotions conveyed by music as well as recognize the melodies and titles of familiar songs (Drapeau, Gosselin, Gagnon, Peretz, & Lorrain, 2009;Hsieh, Hornberger, Piguet, & Hodges, 2011Johnson et al, 2011).…”
Section: Preservation Of Music-evoked Emotions and Memories In Alzheimentioning
confidence: 98%
“…AD patients are also able to perceive and recognize emotions conveyed by music as well as recognize the melodies and titles of familiar songs (Drapeau, Gosselin, Gagnon, Peretz, & Lorrain, 2009;Hsieh, Hornberger, Piguet, & Hodges, 2011Johnson et al, 2011). Importantly, familiar music has consistently been shown to evoke personal emotions and autobiographical memories as well as enhance mood in AD patients (Basaglia-Pappas et al, 2013;Cuddy, Sikka, & Vanstone, 2015;El Haj, Antoine, Nandrino, Gély-Nargeot, & Raffard, 2015;El Haj, Fasotti, & Allain, 2012;Foster & Valentine, 2001;Irish et al, 2006;Meilán García et al, 2012).…”
Section: Preservation Of Music-evoked Emotions and Memories In Alzheimentioning
confidence: 99%
“…67 Previous studies, which have focused more on semantic than on episodic musical memory in AD, found that this kind of memory is partially preserved in such patients. 10,29,[33][34][35]69,70 A recent study also confirmed these findings by demonstrating that the areas crucial to neural encoding of semantic musical memory were less impaired in AD brains. 71 In this paper, we investigated episodic musical memory through the sixth task of the MBEA, which consists of an incidental memory recognition test based on unfamiliar short melodies.…”
Section: Discussionmentioning
confidence: 79%
“…This argues in favor of two independents cognitive processes responsible for semantic verbal and musical memories, which could interact. Despite their ultimate goal of stimulating recollection of autobiographical memories through associated musical memories (MEAMs), Basaglia-Passa et al (2013) built on the semantic musical memory [43] studies of Johnson et al (2011) and Kerer et al (2013). AD patients were asked to hum a familiar song whose title was given.…”
Section: Semantic Musical Memory Vs Semantic Verbal Memorymentioning
confidence: 99%